2008
DOI: 10.1557/proc-1129-v09-02
|View full text |Cite
|
Sign up to set email alerts
|

Erbium Alloyed Aluminum Nitride Films for Piezoelectric Applications

Abstract: Aluminum nitride (AlN) films have been explored for sensor and actuator applications, but the resultant piezoelectric coefficient is still too low to make the films more competitive with more commonly used piezoelectric materials such as lead zirconate titanate (PZT). While AlN does have the disadvantage of a lower piezoelectric response, it does have the ability to maintain its piezoelectric properties above 400°C, something that is not possible with other piezoelectric materials. It is desirable to achieve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This study provides a theorydriven understanding of the fundamental materials science concepts underlying this behavior in addition to experimental realization of predicted property enhancements. Additionally, it provides an opportunity to revisit the results of earlier studies on Al 1−x Sc x N as well as other Al 1−x R x N such as R = vanadium [39], tantalum [39,40], erbium [41], or chromium [42] in a different context, providing fundamental insights to guide future studies of these and other heterostructural alloy systems.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides a theorydriven understanding of the fundamental materials science concepts underlying this behavior in addition to experimental realization of predicted property enhancements. Additionally, it provides an opportunity to revisit the results of earlier studies on Al 1−x Sc x N as well as other Al 1−x R x N such as R = vanadium [39], tantalum [39,40], erbium [41], or chromium [42] in a different context, providing fundamental insights to guide future studies of these and other heterostructural alloy systems.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] While it seems unlikely from an ionic radius perspective that any rare earth cations would be able to incorporate into wurtzite AlN, recent work has showed that Er 3+ and Yb 3+ , much larger cations than Sc 3+ , were substituted successfully at x = 0.015 and up to x ≈ 0.15, respectively. 31,32 In GaN, Yb 3+ can incorporate up to x ≈ 0.3, consistent with the larger radius of Ga 3+ (∼0.47 Å). 33 Incorporating small amounts of Gd 3+ (∼0.94 Å) into wurtzite AlN and GaN has been investigated primarily for optoelectronic applications such as cathodoluminescence and fieldemission devices, 34 given the sharp ultraviolet emission of Gd 3+ at approximately 320 nm and the AlN host lattice as an established optoelectronic material.…”
Section: Introductionmentioning
confidence: 52%
“…26−30 While it seems unlikely from an ionic radius perspective that any rare earth cations would be able to incorporate into wurtzite AlN, recent work has shown that Er 3+ and Yb 3+ , much larger cations than Sc 3+ , were substituted successfully at x = 0.015 and up to x ≈ 0.15, respectively. 31,33 In GaN, Yb 3+ can incorporate up to x ≈ 0.3, consistent with the larger radius of Ga 3+ (∼0.47 Å). 32 Incorporating small amounts of Gd 3+ (∼0.94 Å) into wurtzite AlN and GaN has been investigated primarily for optoelectronic applications such as cathodoluminescence and field-emission devices, 34 given the sharp ultraviolet emission of Gd 3+ at approximately 320 nm and the AlN host lattice as an established optoelectronic material.…”
Section: Introductionmentioning
confidence: 69%
“…After significant effort, Sc 3+ has been substituted into the wurtzite AlN crystal structure at compositions of up to x ≈ 0.43 (i.e., Al 0.57 Sc 0.43 N) before phase separation to the rocksalt ScN end-member crystal structure occurs. ,, Recent work has shown that the solubility of Sc 3+ depends both on ionic size and on ionicity, with Sc–N bonds more ionic than Al–N bonds; however, this ionicity effect is difficult to deconvolute from other effects. Other transition-metal cations such as Cr, Zr, Hf, Y, Ta, and Ni have also been investigated as alloys with AlN, and their properties have been studied. While it seems unlikely from an ionic radius perspective that any rare earth cations would be able to incorporate into wurtzite AlN, recent work has shown that Er 3+ and Yb 3+ , much larger cations than Sc 3+ , were substituted successfully at x = 0.015 and up to x ≈ 0.15, respectively. , In GaN, Yb 3+ can incorporate up to x ≈ 0.3, consistent with the larger radius of Ga 3+ (∼0.47 Å) …”
Section: Introductionmentioning
confidence: 99%